TIPOLOGI ARSITEKTUR FASAD ART DECO PADA BANGUNAN-BANGUNAN DI YOGYAKARTA - , Labdo Pranowo,ST. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Art Deco is one of important architectural styles are present in the architecture of the colonial era in Indonesia. Style that was born in Europe is entering Indonesia through the works of Dutch architect professional practice at the end of the Dutch colonial period. As part of the style that developed in the era of the 20s, this style is growing in popularity in Indonesia and become one of the important peaks kolonal era architecture. Traces on many buildings in cities in Indonesia showed very breadth of this force is applied. Areas and commercial areas in the old city center store many buildings of this style, which is expressed explicitly or vaguely through its elements. This suggests the existence of a wealth of diversity of views in the art deco style building in Indonesia, including Yogyakarta. This research was conducted on 44 buildings scattered around the city of Yogyakarta. Observation and analysis was limited to the facade and the visual elements on the facade of the building. These limits are chosen by considering the number of research objects that will be observed and various levels / intensity of the forces on the building. This study is expected to answer the question